EDUKASI PENCEGAHAN STUNTING DAN KANKER BERBASIS KEARIFAN LOKAL - Laraeni, Yuli; Faiqah, Syajaratuddur; Pratiwi, Intan Gumilang (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Early prevention of stunting is essential to avoid long-term adverse impacts. Efforts to prevent stunting should begin as early as possible, particularly targeting women of reproductive age who are preparing for pregnancy, so that the first 1000 days of life (HPK) for the child can be optimally supported. In addition to stunting, cancer is also a significant public health concern that needs attention. Cancer is a disease caused by abnormal and uncontrolled cell growth. Both of these health problems — stunting and cancer — can actually be prevented through the consumption of nutritious food. The purpose of this community service activity was to provide education on stunting and cancer prevention based on local wisdom. The methods used in this activity included health education on nutritious menu planning, demonstrations of healthy food preparation, and the provision of information on stunting and cancer prevention.The result of this community service activity showed an increase in public knowledge regarding the prevention of stunting and cancer. It is recommended that community participation continues to be enhanced through collaboration with healthcare workers and local government. This collaboration is crucial to continuously remind and encourage residents to consume a balanced and nutritious diet as a collective effort in improving public health.